CPU DB: Recording Microprocessor History. (Communications of the ACM, 2012)
The article focuses on the CPU DB open database containing information of 790 microprocessors from 1971 to 2012. It states that CPU DB contains a number of data entries for each central processing unit (CPU) including physical parameters and performance metrics. It comments on the difficulty of direct comparisons due to the significant improvement of manufacturing technologies and mentions that the database estimates how processor power and performance would scale with technology. It talks about how microchip voltage, power and complexity has scaled over time and mentions that since the release of the Intel 80386 CPU in 1985, transistor area shrank by a factor of nearly 4,000 while transistor count grew by a factor of 16,000.